2016
DOI: 10.1021/acs.jpcb.6b01870
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Comparison of Biomembrane Force Fields: Structure and Dynamics of Model DMPC, POPC, and POPE Bilayers

Abstract: Atomistic molecular dynamics simulations have become an important source of information for the structure and dynamics of biomembranes at molecular detail difficult to access in experiments. A number of force fields for lipid membrane simulations have been derived in the past; the choice of the most suitable force field is, however, frequently hampered by the availability of parameters for specific lipids. Additionally, the comparison of different quantities among force fields is often aggravated by varying si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
177
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(216 citation statements)
references
References 106 publications
28
177
0
Order By: Relevance
“…We note that this is the same approach as described by Pluhackova et al when testing a proposed work-around for known problems within the GROMACS program g_order (also termed gmx order in recent GROMACS versions). 42 We also note here that the CHARMM36 force field simulation was first processed with the GROMACS program trjconv to ensure none of the lipids were split across the periodic boundary, as some of the tools tested (e.g., the calc_op.tcl script and the g_lomepro program) produced slightly incorrect results if this were the case (data not shown).…”
Section: ■ Methodsmentioning
confidence: 99%
“…We note that this is the same approach as described by Pluhackova et al when testing a proposed work-around for known problems within the GROMACS program g_order (also termed gmx order in recent GROMACS versions). 42 We also note here that the CHARMM36 force field simulation was first processed with the GROMACS program trjconv to ensure none of the lipids were split across the periodic boundary, as some of the tools tested (e.g., the calc_op.tcl script and the g_lomepro program) produced slightly incorrect results if this were the case (data not shown).…”
Section: ■ Methodsmentioning
confidence: 99%
“…The particle mesh Ewald summation [64] was applied to compute the long-range electrostatics. For further simulation details see Pluhackova et al [65]. A summary of all atomistic simulations is given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The sources of error include an algorithmic implementation (Section 3.1.1), appropriate choice of constant temperature scheme (Section 3. 105 and Pluhackova et al 106 were unable to reproduce previously published results using the GROMOS 54A7 lipid force field with recent versions of the GROMACS simulation package (versions 4.5, 4.6 and 5.1.2) 69,107 , suggesting that this model may not reproduce the experimentally observed phase properties of phosphatidylcholine lipid bilayers modelled under certain hydration and temperature conditions. Specifically, it was found that the area per lipid was lower and the degree of acyl chain order greater than expected.…”
Section: Discussionmentioning
confidence: 85%
“…This made the reproduction of previous work with later versions of the code no longer possible and led to false claims regarding the performance of the GROMOS 54A7 lipid parameters. 106 We note that Botan et al 105 recognised the discrepancy between different versions of the code and went to considerable lengths to trace the source of the discrepancy as well as highlighted the problem to the developers of the code. That the true cause of the problem was not identified and addressed points to general challenges in the reference conditions used within both the code development community as well as those involved in force-field development and validation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation